Streamflow response to native forest restoration in former Eucalyptus plantations in south central Chile. Issue 8 (10th August 2021) - Lara, Antonio; Jones, Julia; Little, Christian; Vergara, Nicolás
Abstract: Global increases in intensive forestry have raised concerns about forest plantation effects on water, but few studies have tested the effects of plantation forest removal and native forest restoration on catchment hydrology. We describe results of a 14‐year paired watershed experiment on ecological restoration in south central Chile which documents streamflow response to the early stages of native forest restoration, after clearcutting of plantations of exotic fast‐growing Eucalyptus, planting of native trees, and fostering natural regeneration of native temperate rainforest species. Precipitation, streamflow, and vegetation were measured starting in 2006 in four small (3 to 5 ha) catchments with Eucalyptus globulus plantations and native riparian buffers in the Valdivian Coastal Reserve. Mean annual precipitation is 2500 mm, of which 11% occurs in summer. Streamflow increased, and increases persisted, throughout the first 9 years of vigorous native forest regeneration (2011 to 2019). Annual streamflow increased by 40% to >100% in most years and >150% in fall and summer of some years. Streamflow was 50% to 100% lower than before treatment in two dry summers. Base flow increased by 28% to 87% during the restoration period compared to pre‐treatment, and remained elevated in later years despite low summer precipitation. Overall, these findings indicate that removal of Eucalyptus plantations immediately increased streamflow, and native forest restoration gradually restored deep soil moisture reservoirs that sustain base flow during dry periods, increasing water ecosystem services. To our knowledge this is the first study to assess catchment streamflow response to native forest restoration in former forest plantations. Therefore, the results of this study are relevant to global efforts to restore native forest ecosystems on land currently intensively managed with fast‐growing forest plantations and may inform policy and decision‐making in areas experiencing a drying trend associated with climate change. Abstract : This study is the first to test streamflow response to native forest restoration in former fast‐growing Eucalypt forest plantations. Streamflow increased persistently through the first decade of restoration of native forests from planted seedlings and natural regeneration of diverse species. Projected climate change drying trends in south central Chile indicates restoration of native forests is key for the recovery of streamflow and water provision. .